Non-water-suppressed short-echo-time magnetic resonance spectroscopic imaging using a concentric ring k-space trajectory - Emir, U; Burns, B; Chiew, M; Jezzard, P; Thomas, M (Wiley, 2017)
Water-suppressed magnetic resonance spectroscopy (MRS) acquisition techniques have been the standard MRS approach used in research and for clinical scanning to date. The acquisition of a non-water-suppressed MRS spectrum is used for artefact correction, reconstruction of phased-array coil data and metabolite quantification. Here, a two-scan metabolite-cycling spectroscopic imaging (MRSI) scheme is demonstrated and evaluated, that does not use water suppression. Specifically, the feasibility of acquiring and quantifying short-echo (TE = 14 ms), two-dimensional STEAM MRSI spectra in the motor cortex is demonstrated on a 3T MRI system. The increase in measurement time from the metabolite cycling is counterbalanced by a time-efficient concentric ring k-space trajectory. To validate the technique, water-suppressed MRSI acquisitions were also performed for comparison. The proposed non-water-suppressed metabolite-cycling MRSI technique was tested for detection and correction of resonance frequency drifts due to subject motion and/or hardware instability, and the feasibility of high-resolution metabolic mapping over a whole brain slice was assessed. Our results show that the metabolite spectra and estimated concentrations are in agreement between non-water-suppressed and water-suppressed techniques. The achieved spectral quality, signal-to-noise ratio > 20 and linewidth < 7 Hz allowed reliable metabolic mapping of five major brain metabolites in the motor cortex with an in-plane resolution of 10x10 mm2 in 8 minutes and with a Cramér-Rao lower bound of less than 20 % using LCModel analysis. In addition, the high SNR of the water peak of the non-water-suppressed technique enabled voxel-wise single-scan frequency, phase and eddy current correction. These findings demonstrate that our non-water-suppressed metabolite-cycling MRSI technique can perform robustly on 3T MRI systems and within a clinically feasible acquisition time.